The Sociology of Pierre Bourdieu: theoretical potential for the subfield of nursing - Deise Ferreira Souza; Zenith Rosa Silvino
ABSTRACT Objective: to approach the basic conceptions of Pierre Bourdieu's sociology and its articulation with the subfield of nursing by focusing on managerial aspects. Method: reflections are based on the concepts of field, habitus, capital and symbolic power applied to the subfield of nursing by favoring the understanding of organizational dynamics and its agents. Result: health institutions are living structures in the adverse social world where nursing agents' interests express their way of thinking and acting according to the place they occupy in the organization. These spaces of fight and symbolic violence tend to inculcate ideologies that meet these agents' interests. Final Considerations: The proposition theory is fruitful to reflect the practice of management by unveiling the relationships and role that organizations establish about their agents. She warns about the possibility of seeing changes in the subfield of nursing.